Method of histopathology-ultrasound association as a pedagogical strategy for medical students in the identification of the halo sign - Guillen Astete, Carlos Antonio (2020)
Introduction: There are no validated strategies in the teaching of ultrasound as a diagnostic tool in undergraduate medicine students. Given the role that ultrasound plays in the diagnostic capacity of any clinician is currently undeniable, a teaching method is proposed based on the demonstration of the association between the histopathology of a large vessel vasculitis and the characteristic ultrasound finding, known as the «halo sign». Methods: The teaching strategy was imparted by means of a 10-minute video presentation. Twenty-one final-year students from a single medical school participated in a concordance study and a validation test, identifying images corresponding to the halo sign in 120 different cases. The overall sensitivity, specificity and likelihood ratio of the students were also determined. Results: The overall concordance test had a kappa coefficient of 0.749 (SD: 0.11). The kappa concordance was 0.76 with dynamic images, and 0.84 with cross-sectional slices. The overall sensitivity was 89.7%, and the positive predictive value was 92.3%. The likelihood ratio achieved was 7.28. Conclusions: It has been shown that the application of this pedagogical method is useful in teaching the identification of an ultrasound sign to medical students. This study also suggests conditions that could be useful to improve between-observer agreement in both teaching scenarios and multiple observer scientific studies.